The neuroprotective effects of Lutongkeli in traumatic brain injury rats by anti-apoptosis mechanism - Xiao,Qiu-Xia (2022)
ABSTRACT Purpose: To explore the neuroprotective effects of Lutongkeli (LTKL) in traumatic brain injury (TBI) and detect the related mechanism. Methods: TBI model was established with LTKL administration (2 and 4 g/kg/d, p.o.). Motor function of rats was examined by Rotarod test. Nissl staining was used to show neuron morphology. Furthermore, the disease-medicine common targets were obtained with the network pharmacology and analyzed with Kyoto Encyclopedia of Genes and Genomes. Lastly, the predicted targets were validated by real-time polymerase chain reaction. Results: After LTKL administration, neural behavior was significantly improved, and the number of spared neurons in brain was largely increased. Moreover, 68 bioactive compounds were identified, corresponding to 148 LTKL targets; 2,855 genes were closely associated with TBI, of which 87 overlapped with the LTKL targets and were considered to be therapeutically relevant. Functional enrichment analysis suggested LTKL exerted its pharmacological effects in TBI by modulating multiple pathways including apoptosis, inflammation, etc. Lastly, we found LTKL administration could increase the mRNA level of Bcl-2 and decrease the expression of Bax and caspase-3. Conclusions: This study reported the neuroprotective effect of LTKL against TBI is accompanied with anti-apoptosis mechanism, which provides a scientific explanation for the clinical application of LTKL in the treatment of TBI.